Evaluation of the excellent performance of the administrative body members of the first class football league in Iraq - Farhan, Ziyad mishaal; Jawad, Sundus Mousa (International Journal of Psychosocial Rehabilitation, 2020)
The world today is witnessing challenges in various sciences as a result of the continuous development that the world is witnessing, and since the administration is part of this environment, therefore it is natural for workers in Iraqi sports clubs to face some challenges and obstacles that hinder the achievement of their goals that they seek, and to keep pace with this continuous development For administrative operations, it has become imperative for those in charge of sports management to carry out continuous research and development to reach the best administrative methods and means that serve the sports aspects, administrative, technical, infrastructure, media, marketing ... and other resources that have a positive impact on the reality of sports work, given the lack of The existence of a standard for sports institutional excellence, so the researchers believe that it is necessary to develop a standard for Iraqi sports clubs.